2005
DOI: 10.1093/nar/gki364
|View full text |Cite
|
Sign up to set email alerts
|

MicroInspector: a web tool for detection of miRNA binding sites in an RNA sequence

Abstract: Regulation of post-transcriptional gene expression by microRNAs (miRNA) has so far been validated for only a few mRNA targets. Based on the large number of miRNA genes and the possibility that one miRNA might influence gene expression of several targets simultaneously, the quantity of ribo-regulated genes is expected to be much higher. Here, we describe the web tool MicroInspector that will analyse a user-defined RNA sequence, which is typically an mRNA or a part of an mRNA, for the occurrence of binding sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
147
0
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(156 citation statements)
references
References 30 publications
0
147
0
9
Order By: Relevance
“…It has been also recently demonstrated that miR-221/2 family interaction with c-Kit 3'UTR inhibits normal erythropoiesis and erythroleukemic cell growth. 36 It is notewhorthy that 3 out of 9 up-regulated miRNAs (33%) and 7 out of 23 down-regulated miRNAs (30%) are predicted to target c-Kit 3'UTR 5,[37][38][39] (Fig. 1B, dark grey bars): it seems that at least part of affected miRNAs could share a similar function to those initially variated, indicating that a connection among miRNAs with coordinated function exist.…”
Section: Micrornas As Post-transcription Factorsmentioning
confidence: 95%
“…It has been also recently demonstrated that miR-221/2 family interaction with c-Kit 3'UTR inhibits normal erythropoiesis and erythroleukemic cell growth. 36 It is notewhorthy that 3 out of 9 up-regulated miRNAs (33%) and 7 out of 23 down-regulated miRNAs (30%) are predicted to target c-Kit 3'UTR 5,[37][38][39] (Fig. 1B, dark grey bars): it seems that at least part of affected miRNAs could share a similar function to those initially variated, indicating that a connection among miRNAs with coordinated function exist.…”
Section: Micrornas As Post-transcription Factorsmentioning
confidence: 95%
“…As expected, no changes in the luciferase activity were observed in the presence of the miR-1247 mimic, suggesting that miR-1247 does not, indeed, target the SOX9 3Ј-UTR. However, because miRNAs can, in many cases, target the coding sequences (CDS) of mRNAs (24), we screened for possible miR-1247 binding sites in the SOX9 CDS using MicroInspector (25) and RNAhybrid (26), and both programs detected overlapping putative binding sites in positions 525 and 540 of the CDS, respectively (Fig. 6E).…”
Section: Mir-1247 Is Expressed In Mouse Cartilage and Correlates Withmentioning
confidence: 99%
“…Computational analysis using MicroInspector [30] identified a putative binding site for miR-422a in the MLH1 3′-UTR that is disrupted by the 3-nucleotide deletion, suggesting a possible role for miR422a in regulating expression of MLH1. To explore this possibility, HeLa cells were transfected with miR-422a precursor (pre-miR-422a) or anti-miR-422a, and the MLH1 protein level was quantified.…”
Section: Mir-422a Regulates Mlh1 Expression By Interacting With the Mmentioning
confidence: 99%